Evaluation of leucaena populations for tolerance to aluminum. III. Criteria for screening - Maluf, Angela Maria; Martins, Paulo Sodero; Maluf, Wilson Roberto (Pesquisa Agropecuaria Brasileira, 2014)
Due to the fact that multivariate analysis is less convenient than univariate analysis for the study of genetic parameters, a study was undertaken to establish which individual parameters (length of the aerial portion – Y1, length of the longest root - Y2, dry weight of the aerial portion – Y3 dry weight of Roots - Y4, length of the first leaf – Y5, number of lateral branches - Y6, dry weight of the aerial portion/dry weight of roots ratio - Y7, and cotyledon persistence - Y8), under which concentration of Al (0, 3, 6, 9 and 12 ppm), would lead to the classification of leucaena (Leucaena leucocephala (Lam.) de Wit) populations for AI tolerance showing highest similarity to that of the cluster analysis. Similarity between univariate and multivariate classifications was tested by aX2 test in 2 x 2 contingency tables. The highest similarities between these criteria were obtained for the parameters Y1, Y2, Y3, Y4 and Y8, under the concentrations of 6, 9 and 12 ppm. The variable Y8 appears to lead to the most consistant results in the discrimination of Al tolerance, besides being easily evaluated (visually) and permitting a non-destructive minimum handling evaluation.